Assessing Ugandan pork butchers’ practices and their perception of customers’ preferences: A best-worst approach - Heilmann, Martin; Mtimet, Nadhem; Roesel, Kristina; Grace, Delia (2015)
Food-borne diseases are a major concern of developing countries. Among the drivers, rapidly increasing pork consumption deserves increased attention. Yet there is little documentation in Uganda on the context in which pork is produced, marketed and consumed and the implications this may have on public health. This study attempts to assess the current knowledge, attitudes and practices and looks more into butchers’ beliefs about customer preferences. Sixty pork butcheries out of 179 mapped in Kampala were randomly selected. In July 2014 on-site observations were undertaken and butchers were interviewed what they think is the most and the least important attributes to their clients when buying pork meat. Best-worst method with a set of previously identified thirteen attributes was used. Half of the pork purchased by the butchers came from pigs slaughtered in backyards or non-gazetted abattoirs. Raw pork accounted for half of the total pork sold by pork butcheries. The other half was served as cooked pork and usually consumed on-site accompanied by raw vegetables. The majority of butchers use a wooden stump as a cutting surface. Pest animals are present in most butcheries including rodents, birds and flies. Best-worst scores showed that among the attributes butchers revealed as the most important for their customers were: “Meat from the same day”, “Cleanliness in the butchery” and “Trust in butcher“ while “Presence of flies in butchery”, “Age of the animal”, “Pest animals in butchery” and “Fat layer of meat“ were the least significant qualities. Others varied in-between such as “Price”, “Colour of meat”, “Bony meat”, “Butcher wearing coat”, “Type of building structure” and “Butchery close to main road”. The results indicate the need to improve food hygiene in order to mitigate food contamination risks but they also show sellers’ believes which need to be taken into account and addressed. Bringing this research into use will allow targeted interventions and empower butchers to improve the conditions in their shops, strengthen their businesses, and therefore contribute to healthier clients and public health. The research was carried out with the financial support of the Federal Ministry for Economic Cooperation and Development (BMZ), Germany, and the CGIAR Research Programs on Agriculture for Nutrition and Health, and on Policies, Institutions and Markets led by the International Food Policy Research Institute, through the Safe Food, Fair Food project at ILRI.